STUDY OF A COMBINED DEVICE TO REDUCE THE TOXICITY OF EXHAUST GASES OF DIESEL ENGINES, AGRICULTURAL TECHNOLOGY - & et al., Al-Maidi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This study was aimed to reduce the toxicity of exhaust gases from diesel engines used in agriculture. Indicators are provided for a technical assessment of the efficiency of exhaust gas cleaning for diesel engines that have a significant impact on agricultural crops. A scheme for the installation of a common device to reduce the exhaust toxicity of diesel engines on the YaMZ-238 engine was described during the test and a research methodology is presented. The main results obtained during the improved toxicity testing device installed on the ULTZ-700 tractor are given with the YaMZ-238 engine, which fully reflects the efficiency of cleaning emissions. The reliability graphs are designed to characterize cleaning efficiency, and the experimental formulas obtained are given. Technical and economic assessment techniques are provided for exhaust gas rates, which apply to the developed device to reduce toxicity. As a result, the main conclusions of the study were formulated.